Teaching English. Resource pack - Ross, Claire (Londres British Council, 2010)
Inside you will find a selection of articles about teaching methodology and activities to use in class from the free British Council Website for teachers english.
Keywords: Language; Activities; Games; English - foreign language; Teaching; Teacher trainers